Hydric Balance and Locomotor Performance of Native and Invasive Frogs - Roznik, Elizabeth A.; Rodriguez-Barbosa, Camila A.; Johnson, Steve A. (Frontiers in Ecology and Evolution, 2018)
An animal’s physiology should be closely adapted to its environment to optimize organismal function, so physiological traits may be mismatched when animals are introduced to new locations. For introduced amphibians, mismatched traits involving hydric balance or performance across hydric states could have profound impacts on their abundance and distribution, and thus their invasion success. We examined susceptibility to dehydration in invasive Cuban treefrogs (Osteopilus septentrionalis) and two sympatric native treefrogs (Hyla spp.) in Florida, USA, by measuring rates of evaporative water loss, rates of water uptake, and sensitivity of locomotor performance to dehydration. Of the three species, Cuban treefrogs were the most susceptible to dehydration by experiencing the highest rate of evaporative water loss and lowest rate of water uptake. Green treefrogs (H. cinerea) were the most resistant to dehydration by losing water the slowest and gaining water the fastest, and squirrel treefrogs (H. squirella) were intermediate in rates of water loss and uptake. Dehydrating frogs by 20% of their fully hydrated body masses affected the locomotor performance of all species by decreasing maximum jump lengths, decreasing speed, and increasing successive jump lengths. The maximum jump lengths of Cuban treefrogs and green treefrogs were more sensitive to dehydration than those of squirrel treefrogs. Despite this sensitivity, Cuban treefrogs still outperformed both native species in maximum jump length and speed, even when controlling for body size. Consequently, the performance of dehydrated Cuban treefrogs was similar to that of fully hydrated native treefrogs. Our results suggest that Cuban treefrogs are more susceptible to dehydration and its effects than several native competitors; however, they may be able to at least partly compensate for these effects with their large body size, superior locomotor performance, and strong affinity for refugia. Our findings highlight different strategies used by frogs to maintain water balance and suggest that Cuban treefrog densities may be higher in areas with greater moisture availability and habitat complexity, including urban and densely forested areas. Native treefrogs may experience stronger competition and predation from Cuban treefrogs in these areas, which supports anecdotal reports of native frog declines.